POLITICAL-EDUCATIONAL IDEAS OF CONFUCIUS AND MODERN CHINA (Educological discourse, 2014)
This paper investigation the relationship of the contemporary socio-cultural policy in China with the pedagogical ideas of Confucius on education of worthy citizens. Revealed the views of outstanding thinker about formation of the human person, their relationship with the environment and the state.